STP-Based Marketing and Public Perception Shift of Urban Islamic Primary Schools: Introducing the Demand Surplus Indicator - Arief, Moh. Miftahul; Syukur, Fatah; Fahrurrozi, Fahrurrozi; Raharjo, Raharjo; Ihsani, A. Fikri Amiruddin (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to analyze urban community perceptions of Madrasah Ibtidaiyah (MI) in the city of Surakarta, examine the Segmenting–Targeting–Positioning (STP)-based marketing strategies implemented, and identify the internal and external factors influencing their effectiveness within the context of educational competition in urban settings. Design/methods/approach – This study adopts an integrative literature review design combined with limited field observation and documentation at several MIs in Surakarta. Secondary data were obtained from indexed articles, academic books, research reports, and policy documents, while primary data comprised the physical condition of the schools, facilities, promotional media, and student enrollment data. The analysis followed the stages outlined by Whittemore & Knafl (2005) using Kotler’s STP framework. Findings – The results indicate a significant shift in public perception: MIs are now viewed as modern Islamic schools on par with leading public schools, integrating religious values with mastery of science and technology. The application of STP—combining psychographic segmentation, targeting of flagship programs (foreign languages, robotics, life skills), and positioning based on achievements, facilities, and digital publications—has resulted in a demand surplus of applicants. Supporting factors include teacher quality, an integrative curriculum, and program innovations, while constraints involve limited physical capacity and competition from premium private schools. Research implications – The findings provide strategic guidance for MI administrators to strengthen the “modern Islam” image through curriculum innovation, capacity expansion, and optimization of social media, with strategic adjustments tailored to the demographic and psychographic characteristics of the area.